PROBLEMS IN IT SECTOR, SOLUTIONS AND PERSPECTIVES - Ashurova, Muborak (SAMBHRAM XABARNOMASI, 2024)
This article is devoted to measure history of computer science, current issues of IT sector and giving several solutions and theories according to these problems. This article analyzes who creates the IT problems, hardware and software related to IT issues and their valuable solutions. The author informs some promising researches in this direction.